In vivo biochemistry: applications for small molecule biosensors in plant biology - Jones, Alexander M.; Großmann, Guido (Current opinion in plant biology, 2013)
Revolutionary new technologies, namely in the areas of DNA sequencing and molecular imaging, continue to impact new discoveries in plant science and beyond. For decades we have been able to determine properties of enzymes, receptors and transporters in vitro or in heterologous systems, and more recently been able to analyze their regulation at the transcriptional level, to use GFP reporters for obtaining insights into cellular and subcellular localization, and tp measure ion and metabolite levels with unprecedented precision using mass spectrometry. However, we lack key information on the location and dynamics of the substrates of enzymes, receptors and transporters, and on the regulation of these proteins in their cellular environment. Such information can now be obtained by transitioning from in vitro to in vivo biochemistry using biosensors. Genetically encoded fluorescent protein-based sensors for ion and metabolite dynamics provide highly resolved spatial and temporal information, and are complemented by sensors for pH, redox, voltage, and tension. They serve as powerful tools for identifying missing processes (e.g., glucose transport across ER membranes), components (e.g., SWEET sugar transporters for cellular sugar efflux), and signaling networks (e.g., from systematic screening of mutants that affect sugar transport or cytosolic and vacuolar pH). Combined with the knowledge of properties of enzymes and transporters and their interactions with the regulatory machinery, biosensors promise to be key diagnostic tools for systems and synthetic biology.
Gesehen am 19.05.2017